V sosledju strokovnih srečanj je bil izveden že 17. Kongres športa za vse - Berčič, Herman (Šport (Ljubljana), 2024)
In mid-November last year (2023), the 17th “Sport for All” Congress was organised and held in Ljubljana. In the sequence of congresses, the 17th was again “live”, without the constraints of attendance at plenary lectures, roundtables or workshops. The main theme was connected to the challenges and opportunities of sport for all in the local community. This was linked to the thematic contributions, the first referring to the spatial planning of green spaces to promote physical activity in the local environment, and the second to sport for all as one of the most important pillars of the local community. A roundtable entitled “Co-creating the conditions for promoting physical activity in the local community” featured as a specially chosen organisational and thematic format of the Congress. Representing various institutions, organisations, municipal and governmental structures, the participants addressed the central theme from different perspectives. The panellists also importantly contributed to the congress by sharing their experiences and insights from various fields of sport for all in the local community in the thematic segment of good practice examples, from the perspective of users.
Keywords: challenges; conditions; congress; izzivi; kongres; local community; lokalna skupnost; možnosti; opportunities; pogoji; sport; sport for all; šport; Šport za vse